KOMPETENSI KOMUNIKASI WANITA DALAM ORGANISASI KEAGAMAAN MUSLIMAT DAN ‘AISYIYAH DI SURABAYA - Ali Nurdin (Jurnal Riset Komunikasi, 2020)
The purpose of this study is to describe the communication competencies of Muslimat and Aisyiyah organization leaders in Surabaya. Research uses descriptive qualitative type. Data collection techniques are done by interview, observation, and document review. Data were analyzed with flow models through the process of data reduction, presentation, conclusion and verification. The results of this study describe that the communication competencies of the leaders of Muslimat and Aisyiyah in coaching members are implemented in the division of tasks and authority that is structured in the organization. Leader communication competence is implemented in formal and informal cadre processes carried out in a controlled manner and based on collective agreements made between leaders and members. The communication model of the leadership of Muslimat and Aisyiyah organizations is characterized by mutual respect for logical and creative decisions from the agreement of organizational members. The supporting factors for the successful communication of Muslimat and Aisyiyah organizations are the collectivity between members, and the inhibiting factors are the boredom and busyness of the members.